Respuesta :

the answer is in the picture
Ver imagen mooreellie61

Answer:

x = 1

y = 4

Step-by-step explanation:

Divide the second equation by 2

2x/2 + 2y/2 = 6/2

x + y = 3

Subtract the new equation from the first equation you were given

3x + y = 1

x   +  y = 3                       Subtract

2x = - 2                            Divide by 2

2x/2 = -2/2

x = - 1

x + y = 3

-1 + y = 3                             Add 1 to both sides

-1 + 1 + y = 3+ 1                   Combine

y = 4

ACCESS MORE